1985
DOI: 10.1159/000166900
|View full text |Cite
|
Sign up to set email alerts
|

Protein Binding of Disopyramide and Elevated Alpha-1-Acid Glycoprotein Concentrations in Serum Obtained from Dialysis Patients and Renal Transplant Recipients

Abstract: A rapid ultrafiltration technique was used to measure the free (unbound) fraction of disopyramide in serum obtained from 14 normal volunteers, 6 chronic hemodialysis patients, and 10 renal transplant recipients. The disopyramide-free fraction varied more than tenfold at a corresponding total (free plus bound) serum disopyramide concentration of 3 μg/ml and was related to the concentration of an acute-phase protein, alpha-1 -acid glycoprotein (AAG), in patient serum. Moreover, disopyramide-free fraction values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…These effects may be partially reversed by dialysis. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. CYP activity in the kidney is estimated to be 20% of liver activity per gram of tissue.…”
Section: Background Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects may be partially reversed by dialysis. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. CYP activity in the kidney is estimated to be 20% of liver activity per gram of tissue.…”
Section: Background Pharmacokineticsmentioning
confidence: 99%
“…Mechanisms point to circulating inhibitory factors some of which are dialyzable. Patients with advanced CRF Stage IV (GFR [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and Stage V (0-15 ml/min) may behave differently depending whether or not they are on dialysis since these factors may be partially removed by dialysis. Estimating the magnitude of these nonrenal effects is difficult without empirical studies.…”
Section: Expert Opinionmentioning
confidence: 99%
“…David et al (1983) further demonstrated prolonged variability in plasma protein binding in vitro from 20 patients with acute myocardial infarction with a relationship between the unbound DP fraction and plasma AAG concentration. The relationship between the binding of DP and the plasma AAG concentration was also demonstrated by Bredesen & Kierulf (1984) and Haughey et al (1985). Bredesen & Kierulf (1984) found a linear relationship between the AAG concentration and the binding ratio in plasma spiked samples.…”
Section: Resultsmentioning
confidence: 68%
“…The concentration of AAG, an acute phase reactant, is increased in patients with acute myocardial infarction (Piafsky et al 1980), chronic renal failure requiring dialysis, and renal transplant recipients (Haughey et al 1985). This results in reduction of the free fraction of disopyramide in these patients.…”
Section: Protein Bindingmentioning
confidence: 99%